Credibility, flexibility and renewal: The evolution of inflation targeting in Canada - Thomas J. Carter; Rhys R. Mendes; Lawrence Schembri (Bank of Canada, 2018)
In 1991, Canada became the second country to adopt an inflation target as a central pillar of its monetary policy framework. The regime has proven much more successful than initially expected, both in achieving price stability and in stabilizing the real economy against a wide range of shocks. We identify and discuss three factors that have contributed to this performance: (i) the simple, readily understood and consistently applied specification of the inflation target, which, since adoption, has taken the form of a point target inside a symmetric control range; (ii) the establishment of the target in an agreement between the central bank and government, in which inflation control was recognized as a joint duty of both parties, implying key supporting roles for fiscal and macroprudential policy; and (iii) the agreement's regular and thorough review-and-renewal process, which has led to continual improvement based on accumulated experience and advances in the academic literature. Together, these factors have helped anchor inflation expectations around a credible target. This anchoring has in turn made it easier for monetary policy to stay on target, setting a powerful virtuous cycle into motion. An additional benefit is that well-anchored inflation expectations leave monetary policy with greater flexibility to consider its impacts on output and employment variability, as well as financial stability. Nonetheless, certain features of the current economic landscape - including low equilibrium real interest rates and high debt burdens in key sectors - now present monetary policy in Canada and other jurisdictions with significant challenges. We discuss these issues and argue that they require inflation-targeting central banks to give careful thought to the steps that can be taken to refine and strengthen their policy frameworks, widen their toolkits and best ensure complementarity with other macrofinancial policies.
Keywords: E5; E52; E58; E6; E61; 330; Credibility; Inflation targets; Monetary policy; Monetary policy framework